Post-stimulus endogenous and exogenous oscillations are differentially modulated by task difficulty - Li, Yun; Lou, Bin; Gao, Xiaorong; Sajda, Paul (Frontiers in Human Neuroscience, 2013)
We investigate the modulation of post-stimulus endogenous and exogenous oscillations when a perceptual decision is made more difficult. We use exogenous frequency tagging to induce steady-state visual evoked potentials (SSVEP) while subjects perform a face-car discrimination task, the difficulty of which varies on a trial-to-trial basis by varying the noise (phase coherence) in the image. We simultaneously analyze amplitude modulations of the SSVEP and endogenous alpha activity as a function of task difficulty. SSVEP modulation can be viewed as a neural marker of attention toward/away from the primary task, while modulation of post-stimulus alpha is closely related to cortical information processing. We find that as the task becomes more difficult, the amplitude of SSVEP decreases significantly, approximately 250-450ms post-stimulus. Significant changes in endogenous alpha amplitude follow SSVEP modulation, occurring at approximately 400-700ms post-stimulus and, unlike the SSVEP, the alpha amplitude is increasingly suppressed as the task becomes less difficult. Our results demonstrate simultaneous measurement of endogenous and exogenous oscillations that are modulated by task difficulty, and that the specific timing of these modulations likely reflects underlying information processing flow during perceptual decision-making.